Mukoepidermoid-Karzinom der Speicheldrüsen nach hochdosierter Radioiodtherapie = Mucoepidermoid carcinoma of the salivary glands after high dosage radiotherapy - Henze, Marcus; Hittel, Jens-Peter (Laryngo-Rhino-Otologie, 2001)
Abstract: BACKGROUND: High-dose radioiodine therapy following total thyroidectomy is standard for patients suffering from differentiated thyroid carcinoma...
Gesehen am 25.10.2017